Factors influencing word of mouth generation in the medical tourism industry - Ching, Ying Tian (2023)
The success of the hospitals engaged in medical tourism, where people travel abroad to obtain medical services, depends on their capabilities in retaining the existing customers apart from attracting new customers. By delivering high quality of service and creating superior customer value, it can lead to customer satisfaction, which in turn influences the customer willingness to perform recommendations. Word-of-mouth is a free form of promotion, which is essential, and offers a way to obtain a significant competitive advantage for the hospitality and tourism industry. The purpose of this research is to examine the effect of medical service quality, perceived value and medical tourist satisfaction on word-of-mouth generation in medical tourism marketing. This study also attempts to investigate the mediating role of trust. A self-administered questionnaire was used to test the conceptual framework. Partial Least Squares Structural Equation Modelling (PLS-SEM) was used to assess the measurement model and the structural model. The findings showed that perceived value is positively related to medical tourist satisfaction, while medical tourist satisfaction is positively related to trust and word-of-mouth generation. The findings also revealed that trust is positively related to word-of-mouth generation. Additionally, trust was found to have a significant mediating effect. Surprisingly, no positive relationship was discovered between medical service quality and perceived value, nor between medical service quality and medical tourist satisfaction. The results of this study provide crucial implications for Malaysian government and medical service providers in developing effective strategies on how to stimulate medical tourists’ word-of-mouth generation. This research further provides a reference point for future scholar in examining the word-of-mouth behaviour of medical tourists.